Broad‐spectrum next‐generation sequencing‐based diagnosis of a case of Nager syndrome. Issue 9 (14th June 2020) - Zhao, Jue; Yang, Liwei
Abstract: Background: Nager syndrome is a rare genetic syndrome characterized by craniofacial and preaxial limb anomalies. Haploinsufficiency of the SF3B4 gene has been identified as a significant reason for Nager syndrome. Treacher Collins syndrome (TCS) has similar facial features; however, the TCOF1, POLR1D, and POLR1C genes have been reported as the critical disease‐causing genes. Similar phenotypes make it easy to misdiagnose. Case report: In this report, we have presented a case of one newborn with acrofacial dysostosis, who was first diagnosed with TCS. Expanded next‐generation sequencing eventually detected a (c.1A>G) heterozygous mutation in the SF3B4 gene at chr1:149899651 that was confirmed by Sanger sequencing. Combined with his preaxial limb anomalies discovered after his death, a diagnosis of Nager syndrome was made. Conclusions: This report presents one patient with Nager syndrome who was initially misdiagnosed with TCS. Correct genetic testing will be beneficial to future prenatal diagnosis.